Clonally expanded CD8 T cells patrol the cerebrospinal fluid in Alzheimer's disease: Molecular and cell biology: Inflammatory and microglia‐mediated mechanisms in AD. (7th December 2020) - Gate, David; Saligrama, Naresha; Levanthal, Olivia; Davis, Mark; Wyss‐Coray, Tony
Abstract: Background: Alzheimer's disease (AD) is an incurable neurodegenerative disorder in which neuroinflammation plays a critical function. Yet, little is known about the contribution of the adaptive immune response in AD. Here we used integrated analyses of multiple cohorts to identify peripheral and central adaptive immune changes in AD. Method: First, we performed mass cytometry of peripheral blood mononuclear cells and discovered an immune signature of AD consisting of increased numbers of CD8 + T effector memory CD45RA + (TEMRA ) cells. Result: In a second cohort, we found that CD8 + TEMRA cells were negatively associated with cognition. Furthermore, single cell RNA sequencing revealed their enhanced T cell receptor (TCR) signaling. Notably, by utilizing multiple single cell TCR sequencing strategies on a third cohort, we discovered clonally expanded CD8 + TEMRA cells in patient cerebrospinal fluid (CSF). Finally, we used machine learning, cloning, and peptide screens to demonstrate specificity of clonally expanded AD CSF TCRs to two separate Epstein‐Barr virus antigens. Conclusion: These results reveal a novel blood‐CSF adaptive immune response in AD and provide evidence of clonal, antigen‐experienced T cells patrolling the intrathecal space of brains affected by age‐related neurodegeneration.